The intestinal microbiome as a separate organ - Yu. O. Shulpekova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To discuss functions of intestinal bacteria as a part of the «host» body basing on the present-time publications, to consider interaction of bacteria with macroorganism, which reminds intercellular cooperation by its nature.Key points. Intestinal microbiome encompasses about 1014 microorganisms, over 99% of microbiome genetic material belong to bacteria. In healthy people three basic enterotypes (according to the type of dominating species) are defined. The pattern of small intestine microflora is studied much poorly, than that of the large intestine. Due to difference in sampling methods it is difficult to draw clear-cut conclusions on microflora role in pathogenesis for scientific investigations. Analysis of sequential cloning of 16S ribosomal RNA possesses the highest information value of all up-to-date methods. Interaction of bacteria with the «host» reminds cooperation of usual cells and can be carried out due to receptor binding, paracrine and humoral pathways, as well as due to phagocytosis and endocytosis. Microbes produce hormone-like substances, analogues of growth factors and neurotransmitters that determine two-way interaction of microflora with the central nervous system and its active metabolic role. The microbiome dynamically reacts to environmental changes, including stress. Studing of intestinal microbiome impact in development of visceral hypersensitivity, regulation of intestinal motility and sensitivity is quite promising trend.